Electronic structure of electron-irradiated graphene and effects of hydrogen passivation. (12th September 2018) - Weerasinghe, Asanka; Ramasubramaniam, Ashwin; Maroudas, Dimitrios
Abstract: We report results for the electronic structure of irradiated and irradiation-induced amorphized graphene based on first-principles density functional theory calculations, using models of irradiated graphene sheets that were initially relaxed structurally according to molecular-dynamics simulations. We find that localized states appear at the Fermi level upon irradiation damage and the corresponding local density of states increases with increasing defect density. Electronic structure calculations show that band flattening occurs due to electron localization in the vicinity of irradiation-induced defects and reduces the charge carrier mobility. This band flattening effect becomes stronger with increasing defect density due to a greater degree of carrier localization at irradiation-induced carbon dangling bonds. Passivating these dangling bonds with hydrogen atoms delocalizes the charge density, reduces the density of states at the Fermi level, and increases the band dispersion. Hydrogen passivation also has the additional effect of quenching any localized magnetic moments at dangling bonds. Our studies show that defect engineering of graphene—even at a gross level without atomic-scale precision—can be employed to tune its properties for additional electronic functionality.